2016
DOI: 10.1007/978-3-319-23573-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate and Toxicology of Dimethoate

Abstract: The insecticide dimethoate, an organophosphate, was first introduced in 1962 for broad spectrum control of a wide range of insects including mites, flies, aphids, and plant hoppers. It inhibits AChE activity, resulting in nerve damage, which may lead to death. It is considered highly toxic to insects although dimethoate resistance has been observed. Dimethoate has both a low vapor pressure (0.247 mPa) and Henry's law constant (l.42x10(-6) Pa m3/mol), thus volatilization is not a major route of dissipation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The half-life of dimethoate in clay loam soil was determined to be 10 and 5 days at 10°C and 20°C, respectively. This confirmed a faster decrease in the pesticide due to the increased temperature [9]. HPLC analysis was carried out to check degradation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The half-life of dimethoate in clay loam soil was determined to be 10 and 5 days at 10°C and 20°C, respectively. This confirmed a faster decrease in the pesticide due to the increased temperature [9]. HPLC analysis was carried out to check degradation.…”
Section: Discussionmentioning
confidence: 72%
“…Organism SS3 c showed the best degradation potential and HPLC (High Performance Liquid Chromatography) analysis was carried out for the sample degraded by the organism. Dimethoate adsorption was measured on eight soil types (pH from 8.0-8.45; OM from 0.73-2.95%; clay content from 5.9-14.9%) in which resulting isotherms followed an L-shape [9]. Some pesticides hydrolyze very rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The 96‐h EC50s of dimethoate that indicate higher toxicity at test series PEST + nTiO 2 than at test series PEST despite more efficient degradation (Table 4) could, in addition, be induced by the formation of metabolites that are more toxic than the parent substance (Evgenidou et al 2006; Farner Budarz et al 2017). It was shown that during photocatalytic degradation with nTiO 2 , dimethoate is degraded into 9 by‐products (Evgenidou et al 2006), whereas the major by‐product, omethoate (Van Scoy et al 2016), is 90‐fold more toxic than the mother compound (Pesticide Properties Database; Lewis et al 2016). Likewise, the photocatalysis (UV = 5.8 W/m 2 ; TiO 2 = 120 mg/L) of malathion sharply increases its toxicity toward Vibrio fischeri , whereas no increase in toxicity was observed when treating malathion with UV alone (Li et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to dimethoate's high water solubility and low soil persistence, its potential to runoff into surface waters and leaching into groundwater is high [15]. The most important degradation pathways of dimethoate in the environment are hydrolysis, photolysis and microbiological degradation [15].…”
Section: Figurementioning
confidence: 99%
“…Due to dimethoate's high water solubility and low soil persistence, its potential to runoff into surface waters and leaching into groundwater is high [15]. The most important degradation pathways of dimethoate in the environment are hydrolysis, photolysis and microbiological degradation [15]. The photocatalytic oxidation and microbial metabolism of dimethoate often have omethoate as the final product, which is not desirable due to its extreme toxicity.…”
Section: Figurementioning
confidence: 99%